고품질 중간찰 향미벼 ‘골든퀸 3호’ - 장성규(Seong-Gyu Jang); 이원도(Wondo Lee); 박용진(Yong-Jin Park); 이영상(Young-Sang Lee); 이주현(Joohyun Lee); 서정환(Jeonghwan Seo); 조유현(Yoo-Hyun Cho); 권순욱(Soon-Wook Kwon) (Korean journal of breeding, 2021)
‘Golden queen 3’, an aromatic rice variety, was developed by Seedpia inc. (Suwon, Korea) breeding company in 2014. This cultivarwas derived from a cross between ‘HJ-11’, a high-yield, aromatic line, and ‘JCH33M-15-1-9-1’, which has a low amylose content. Duringthe F3-F8 generation, breeding lines were selected using a pedigree breeding method. The most promising line (JS9-3-73-15-5-1-5-3-1-1) wasadvanced and named ‘SP005’ in 2013. This variety was headed on August 13, two days later than ‘Hwayeong’ in the ‘in middle plane’is commonly used to distinguish rice cultivation areas in Korea, so I think it's no problem to the understanding for readers (including farmers). The culm and panicle lengths of this variety were 75.7 cm and 20.1 cm, respectively. It has approximately 14.7 tillers per hill and 104.8spikelets per panicle, and the 1000-grain weight was 21.8 g. The yield performance was 5.47 MT/ha in the local adaptability test, and theamylose content of this variety was 12.5%. 2-Acetyl-1-pyrroline was detected as the major volatile ingredient in aromatic rice, and a 1 bpinsertion on the 14th exon (badh2.7 allele) was identified in the Badh2 gene. (Registration No. 7308). KCI Citation Count: 0